Environmental effects of anthropogenic waste on intestinal nematode parasites of murid rodents in Istria, Croatia - Bužan, Elena; Čabrilo, Borislav; Ivović, Vladimir; Bjelić Čabrilo, Olivera (Biologia Serbica, 2019)
The quantity and extent of municipal solid waste is rising as urbanization, mass consumption, and consumer lifestyles have become more prevalent worldwide. Many cities cannot effectively manage their own waste, which leads to the creation of illegal waste sites. We investigated the potential effects of illegal waste dumping on the qualitative and quantitative characteristics of rodent-parasite communities in semi-natural habitats. In particular, we studied spatial host-parasite turnover rates as a function of urbanization and the presence of illegal waste sites for four species of the family Muridae: house mouse (Mus musculus), wood mouse (Apodemus sylvaticus), striped field mouse (A. agrarius), and yellow-necked mouse (A. flavicollis). Eleven species of intestinal nematodes were found, with varying levels of prevalence, mean infection intensity and mean abundance in different habitat types. We found that the composition of parasite communities did not depend on the level of habitat degradation, although it did depend on the host community structure. Generalized Linear Model analysis showed that there was no relationship between negative anthropogenic disturbances of natural habitat and parasite abundance. However, the prevalence of Syphacia stroma, S. frederici, S. obvelata, Heterakis spumosa and Rictularia proni was significantly different between different types of habitat disturbance. These results suggest that human disturbances affect the presence and species composition of intestinal nematodes of mice at specific sites, although further and more systematic research on a larger scale is necessary.